The Development of the Law of the Sea by UNCLOS Dispute Settlement Bodies - Ngoc Nguyen, Lan (Cambridge University Press, 2023)
"This book is for researchers and postgraduate students of international law, particularly the law of the sea, as well as practitioners and government advisors. It provides a critical assessment of the ways by which UNCLOS tribunals develop the law of the sea and explores the factors that explain such development"--